The shape grammar of Rudinara Residence - Ramli, Mohd. Adib (2010)
This study aims to explore a new application of shape grammar formalism and to contribute to the existing body of knowledge as all the previous shape grammar projects only revolve around two issues. The first issue is on the shape of building plans they analyzed where all of them involve a rectangular plan or a form resulting from a combination of several rectangular shapes. The second issue is on the building category they chose which concerns with traditional or famous older styles. For that reason Rudinara residence was chosen as a subject for this study as it has triangular plans as well as contemporary architectural style. Shape grammar is a method used to analyze existing design language or style and subsequently using the design principles to create a multiple of new and diverse designs in the same style. In addition, it is also used to produce new and original languages of design as well as to transform an existing language into a new one. Therefore, two groups of data were required for this study with regard to the shape grammar formalism and also the existing design of Rudinara. Basic information regarding this method was presented prior to its application on Rudinara. Subsequently, three models of previous shape grammar applications which are comparable with this study were reviewed to give directions for the creation of the shape grammar of Rudinara. Then, the existing design of Rudinara was analyzed and the findings were successfully translated in terms of diagrammatical shape rules together with the explanations. The rules, totaling fifty altogether, describes the relationship and connection between each main building component. Later, the rules were applied to create new designs in the same language as Rudinara and as a result, a minimum of forty new and diverse designs were achieved. Six of the new designs were chosen to be described in detail afterwards. The step by step processes of applying the rules to create the new designs were presented as well as the detail plans and three-dimensional computer models. The purpose was to give clear impressions on how the new designs actually look like, thus they can be compared with Rudinara in terms of their design style. This study has contributed on the exploration of various design possibilities in the architectural style of Rudinara besides expanding the usage of this style in Malaysia’s architectural landscape. Furthermore, this style as well as the application of shape grammar method in designing can be commercialized in a form of publication especially in Malaysia. Furthermore, courses and lectures on shape grammar can possibly be offered in local architectural schools to promote the use of this alternative method as well as encouraging students to establish their own style.